Effects of observing real, animated and combined model on learning cognitive and motor levels of basketball jump shot in children - Ghavami Akbar; Samadi Hossein; Dana Amir; Ghorbani Saeed (Biomedical Human Kinetics, 2022)
Study aim: The purpose of the present study was to investigate the effects of observing the real, animated and combined model demonstrations on cognitive and motor learning of a basketball jump shot.